Dual-linking free-flap reconstruction for above-knee amputation stump coverage in an older patient: a case report - Chang Hoon Jeong; Jeonghee Kim; Hyeokjae Kwon; Sunje Kim; Seung Han Song; Sang-Ha Oh; Yooseok Ha (Archives of Hand and Microsurgery, 2026)
Durable soft tissue coverage is essential for prosthetic rehabilitation after major lower-limb amputation. We report circumferential above-knee amputation (AKA) stump reconstruction using dual-linking free flaps in an 86-year-old man with bilateral lower-extremity crush injuries. The right AKA stump developed circumferential soft tissue loss with near-total femoral exposure. After debridement, reconstruction was performed using a muscle-sparing latissimus dorsi (msLD) flap and an anterolateral thigh (ALT) flap. The msLD flap was anastomosed to the descending branch of the lateral femoral circumflex artery, and the ALT flap was sequentially anastomosed to the serratus branch of the thoracodorsal artery. Both flaps survived without vascular compromise, providing durable, pliable coverage. Minor skin-graft loss at the ALT donor site healed conservatively. At 3 months, the patient ambulated with bilateral prostheses, with stable socket fit and no ulceration. Dual-linking free flaps may provide reliable circumferential coverage and facilitate prosthetic rehabilitation after extensive AKA stump defects.